In-Situ Investigation of Copepod Predators of Ichthyophthirius multifiliis Theronts from Fish-Farming Pond - Lijun Wang; Bingwen Xi; Kai Chen; Jun Xie; Liangkun Pan (Microorganisms)
Ichthyophthirius multifiliis, a parasitic ciliate, causes “white spot disease” in freshwater fish and poses a significant threat to global freshwater aquaculture. Eliminating the free-swimming theront stage from the aquaculture environment is a critical measure for controlling I. multifiliis infections. The natural predator of I. multifiliis theronts in fish-farming ponds were identified using fluorescent dye-labelled live theronts and quantitative PCR; meanwhile, the zooplankton community composition in the positive ponds of I. multifiliis detected by quantitative PCR were analyzed by eDNA metabarcoding assay. The results revealed predation on theronts by cyclopoid copepods, including Cyclops vicinus, Thermocyclops taihokuensis, Cyclops sp., Thermocyclops sp., Eucyclops sp., and Mesocyclops sp. from the in-situ predation aquatic ecosystem, and among these copepods, C. vicinus was identified as a natural dominant predator of I. multifiliis. This study provides a scientific basis for further exploration and utilization of natural predators to enhance sustainable and environmentally friendly control strategies against I. multifiliis.